The Influence of Human Resource Development and Work Motivation on Job Satisfaction at PT. Istana Bukit Kencana Makmur - Luruk Berek, Hildegardis Mariana; Nurul Hermina (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to determine the effect of human resource development and work motivation on job satisfaction of employees of PT. Istana Bukit Kencana Makmur. The research method used in this research is a quantitative approach. The population in this study were all employees at PT. Istana Bukit Kencana Makmur which amounted to 150 employees. The sampling technique used the Slovin formula so that the total sample used was 60 employees. While the data collection technique uses a questionnaire distributed to employees. The data analysis technique used in this research is multiple linear regression analysis, coefficient of determination, and T test with the help of the SPSS program. The results of this study indicate that the variables of human resource development and work motivation have a significant effect on employee job satisfaction.